The effect of dance on depressive symptoms in nursing home residents - Vaňková, Hana; Holmerová, Iva; Macháčová, Kateřina; Volicer, Ladislav; Veleta, Petr; Čelko, Alexander Martin (Journal of the American Medical Directors Association, 2014)
OBJECTIVE: To evaluate the effect of a dance-based therapy on depressive symptoms among institutionalized older adults. DESIGN: Randomized controlled trial. SETTING: Nursing homes. PARTICIPANTS: Older adults (60 years or older) permanently living in a nursing home. INTERVENTION: Exercise Dance for Seniors (EXDASE) Program designed for the use in long-term care settings performed once a week for 60 minutes for 3 months. MEASUREMENTS: Baseline measures included sociodemographic characteristics, ability to perform basic as well as instrumental activities of daily living, basic mobility, self-rated health, and cognitive status. Outcome measures were collected before and after the intervention and included assessment of depressive symptoms using the geriatric depression scale (GDS). RESULTS: Comparison of participants with MMSE of 15 or higher showed that GDS scores in the intervention group significantly improved (P = .005), whereas the control group had a trend of further worsening of depressive symptoms (P = .081). GLM analysis documented highly statistically significant effect of dance therapy (P = .001) that was not influenced by controlling for intake of antidepressants and nursing home location. Dance therapy may have decreased depressive symptoms even in participants with MMSE lower than 15 and resulted in more discontinuations and fewer prescriptions of antidepressants in the intervention group than in the control group. CONCLUSION: This study provides evidence that dance-based exercise can reduce the amount of depressive symptoms in nursing home residents. In general, this form of exercise seems to be very suitable and beneficial for this population.
Keywords: senioři nad 80 let; Socioeconomic Factors; Humans; lidé; deprese; Czech Republic; lidé středního věku; Treatment Outcome; Depression; pečovatelské domovy; Middle Aged; Aged, 80 and over; tanec; Nursing Homes; Female; Male; výsledek terapie; mužské pohlaví; socioekonomické faktory; Aged; ženské pohlaví; Česká republika; Dancing; senioři